2000
DOI: 10.1042/bj3460133
|View full text |Cite
|
Sign up to set email alerts
|

Endoproteolytic processing of integrin pro-α subunits involves the redundant function of furin and proprotein convertase (PC) 5A, but not paired basic amino acid converting enzyme (PACE) 4, PC5B or PC7

Abstract: Several integrin alpha subunits undergo post-translational endoproteolytic processing at pairs of basic amino acids that is mediated by the proprotein convertase furin. Here we ask whether other convertase family members can participate in these processing events. We therefore examined the endoproteolysis rate of the integrin subunits pro-alpha5, alpha6 and alphav by recombinant furin, proprotein convertase (PC)5A, paired basic amino acid converting enzyme (PACE)4, PC1, PC2 and PC7 in vitro and/or ex vivo afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 49 publications
6
60
0
Order By: Relevance
“…Furin is relatively inefficient in processing L1 to yield a 140-kDa fragment, and other proprotein proteases do not cleave L1. A similar result was obtained for the processing of integrin pro-␣-subunits: PC5A is more active than furin, whereas PC1, PC2, PACE4, PC7, and PC5B are inactive (38). In addition, although furin and other proprotein convertases do not efficiently process members of the transforming growth factor-␤ superfamily, PC5A appears to be responsible for the in vivo processing of these proteins (49).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Furin is relatively inefficient in processing L1 to yield a 140-kDa fragment, and other proprotein proteases do not cleave L1. A similar result was obtained for the processing of integrin pro-␣-subunits: PC5A is more active than furin, whereas PC1, PC2, PACE4, PC7, and PC5B are inactive (38). In addition, although furin and other proprotein convertases do not efficiently process members of the transforming growth factor-␤ superfamily, PC5A appears to be responsible for the in vivo processing of these proteins (49).…”
Section: Discussionsupporting
confidence: 55%
“…Coexpression of wild-type L1 with furin, PC1, PC2, PACE4, or PC7 showed no increase in the amount of the 140-kDa fragment (data not shown), confirming that PC5A is the most efficient L1-cleaving proprotein convertase. This difference in cleavage efficiency is not due to different expression levels of each proprotein convertase, as shown previously in other studies (38,41,42). In contrast to the expression of wild-type L1, no 140-kDa fragment was found in the cell pellet (Fig.…”
Section: Mutation Of the Proprotein Convertase Recognition Motif Abrosupporting
confidence: 44%
See 1 more Smart Citation
“…The in vitro study showed that furin is present in THP-1-derived macrophages, and cell-surface expression of integrin a v b 3 is enhanced during the maturation of monocytes to macrophages. Moreover, furin was identified as the major a v convertases [67]. Microscopy studies have shown the co-localization of integrins a v b 3 and its ligand vitronectin in the atherosclerotic intima [68].…”
Section: Furin Recruits Inflammatory Cells and Vsmcs Via Activation Omentioning
confidence: 99%
“…Some integrin ␣ chains undergo a post-translational cleavage in their extracellular domain by furin and PC5A, two proprotein convertases (PCs) of the subtilisin/kexin family. 8,9 The role of this cleavage in integrin function remains unclear. Arguably, this post-translational processing of the ␣ chain is not required for ligand binding, 10 -12 but is essential for the signaling function of ␣6␤1 and ␣v␤5 integrins.…”
mentioning
confidence: 99%